State of knowledge for invasive green iguanas in Florida reveals negative impacts and pervasive research needs - Natalie M. Claunch; Paulina M. Jones; Emily S. Khazan; Bryan M. Kluever (Frontiers in Amphibian and Reptile Science, 2025)
Green iguanas (Iguana iguana), large-bodied lizards native to South and Central America, have established multiple invasive populations worldwide. Where established, invasive green iguanas have negative impacts on private property, agriculture and horticulture, infrastructure and human safety, and the natural environment. Most attempts to formally quantify impacts of invasive green iguanas have been conducted in Puerto Rico, or are limited to singular reports. Green iguanas have been established in Florida since 1966 and currently pose a high management concern which must be informed by research on control methods. Impact data from Florida to justify these efforts are often anecdotal or out of date. Here we present a contemporary review of known and potential impacts of green iguanas to multiple sectors in Florida over time and space. We leverage data accessed from various stakeholders, including nuisance wildlife report data collected from the Florida Fish and Wildlife Commission’s Wildlife Impact Management Section, conflict reports from the USDA Wildlife Services Management Information System, wildlife strike reports from the Federal Aviation Administration, fault reports from energy companies, and observations from natural resource managers. We identify important knowledge gaps in quantifying the scope and magnitude of green iguana impacts necessary to guide future management actions.